Application of electronic educational resources in the preparation process for would be teachers of technologies - Galagan, I. (Journal of Education, Health and Sport, 2019)
The article considers the use of electronic educational resources, as well as testing the feasibility of methods of applying this technology in the training of future teachers of technology. It is emphasized that updating and improving the forms, methods and means of teaching in higher pedagogical school significantly increase the level of information technology training of future specialists in technological education. In particular, electronic educational resources are used to simulate complex real events, situations, visualization of abstract information by dynamic representation of processes, demonstration of fragments of programs, movies, virtual tours and more. IT software allows modern teachers of technology education to combine text, graphics, animation, video and audio information, which significantly increases the level of learning material.In the conditions of integration of modern Ukraine into the European educational space, the form, methods and means of teaching in the higher pedagogical school need to be updated and unambiguously improved. The constant growth of educational information, the need for its analysis, assimilation, generalization, systematization and preservation, expanding the capabilities of the global Internet have led to the widespread introduction of information technology in the training of future professionals in higher education. After all, without knowledge of multimedia technologies, the ability to develop elements of e-educational resources, navigate in the modern information global space, it is impossible to achieve a high level of professionalism and become a competitive specialist.The application of technology of development and use of electronic educational resources can increase the effectiveness of active teaching methods for all forms of organization of the educational process in higher pedagogical institutions: at the stage of independent training of students, lectures, seminars, practical and laboratory classes.